2012
DOI: 10.1080/13504851.2011.615724
|View full text |Cite
|
Sign up to set email alerts
|

Comparing business R&D across countries over time: a decomposition exercise using data for the EU 27

Abstract: This article develops a simple decomposition of Business R&D Expenditures (BERD) panel data and applies it to analyse the development of R&D intensities in the business sector in the EU 27 countries and important non-EU countries over time. The results show that changes in aggregate BERD figures are driven by 'within' and 'between' effects that differ considerably across countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The findings of this study are in line with findings in [94], where the structural effects have the greatest influence on R&D spending in the top performing countries in this analysis (and the opposite is true for the worst performers). They are also in line with [95], where it was found that Germany is experiencing a structural change towards technology-intense industries, whereas Denmark, Austria, and Sweden have experienced changes in the intrinsic effects. Another study [96] found that industrial specialization was the main driver of R&D intensity across countries (sample included 18 countries and 21 sectors).…”
Section: Checking For Robustnesssupporting
confidence: 86%
“…The findings of this study are in line with findings in [94], where the structural effects have the greatest influence on R&D spending in the top performing countries in this analysis (and the opposite is true for the worst performers). They are also in line with [95], where it was found that Germany is experiencing a structural change towards technology-intense industries, whereas Denmark, Austria, and Sweden have experienced changes in the intrinsic effects. Another study [96] found that industrial specialization was the main driver of R&D intensity across countries (sample included 18 countries and 21 sectors).…”
Section: Checking For Robustnesssupporting
confidence: 86%
“…Much attention has been paid to the compositional structure of European industry (Mathieu and van Pottelsberghe de la Potterie, 2010, Reinstaller and Unterlass, 2012, Cincera and Veugelers, 2013. It has been emphasized that EU member states could pursue the 3% target by changing their industrial structure, in favour of high-tech industries, rather than boosting the R&D intensities of firms in low-or medium-tech sectors.…”
Section: Introductionmentioning
confidence: 99%
“…However, knowing whether a country -relative to an average of R&D intensive benchmark countries-is R&D intensive or not given its industrial structure, allows for an assessment of its position on the segments of an industry in terms of its knowledge intensity. This indicator can also be used as a weighting scheme for structural change indicators (Reinstaller and Unterlass, 2012), adding an outcome dimension. As such, it could serve as a proxy for an outcome indicator when used in conjunction with structural change indicators.…”
Section: Measuring Structural Change and Structural Upgradingmentioning
confidence: 99%